$^{40}$Ar/$^{39}$Ar geochronology of crustal deformation - Monié, Patrick; Münch, Philippe; Milesi, Gaétan; Bonno, Michael; Iemmolo, Arthur (Comptes Rendus. Géoscience)
Crustal deformation is characterized by brittle and ductile faults that accommodate at different scales the strain imposed by plate tectonics. The aim of this contribution is to show with the help of different examples how the in situ $^{40}$Ar/$^{39}$Ar dating of synkinematic neocrystallized minerals in ductile shear zones and the step-heating $^{40}$Ar/$^{39}$Ar dating of synkinematic authigenic clays in fault gouges can bring information on the timing of fault activity. However, due to their complex evolution, interpretation of the argon signature in fault zones requires consideration of several effects among which re- or neocrystallization, inheritance and fluid interaction processes are dominant.